Secondary radiation measurements for particle therapy applications: charged particles produced by 4He and 12C ion beams in a PMMA target at large angle. (7th March 2018) - Rucinski, A; Battistoni, G; Collamati, F; De Lucia, E; Faccini, R; Frallicciardi, P M; Mancini-Terracciano, C; Marafini, M; Mattei, I; Muraro, S; Paramatti, R; Piersanti, L; et al.
Abstract: Proton and carbon ion beams are used in the clinical practice for external radiotherapy treatments achieving, for selected indications, promising and superior clinical results with respect to x-ray based radiotherapy. Other ions, like 4 H e have recently been considered as projectiles in particle therapy centres and might represent a good compromise between the linear energy transfer and the radiobiological effectiveness of 12 C ion and proton beams, allowing improved tumour control probability and minimising normal tissue complication probability. All the currently used p, 4 H e and 12 C ion beams allow achieving sharp dose gradients on the boundary of the target volume, however the accurate dose delivery is sensitive to the patient positioning and to anatomical variations with respect to photon therapy. This requires beam range and/or dose release measurement during patient irradiation and therefore the development of dedicated monitoring techniques. All the proposed methods make use of the secondary radiation created by the beam interaction with the patient and, in particular, in the case of 12 C ion beams are also able to exploit the significant charged radiation component. Measurements performed to characterise the charged secondary radiation created by 12 C and 4 H e particle therapy beams are reported. Charged secondary yields, energy spectra and emission profiles produced in a poly-methyl methacrylate (PMMA) target by 4 H e and 12 C beams of different therapeutic energies were measured at 60° and 90° with respect to the primary beam direction. The secondary yield of protons produced along the primary beam path in a PMMA target was obtained. The energy spectra of charged secondaries were obtained from time-of-flight information, whereas the emission profiles were reconstructed exploiting tracking detector information. The obtained measurements are in agreement with results reported in the literature and suggests the feasibility of range monitoring based on charged secondary particle detection: the implications for particle therapy monitoring applications are also discussed.